Dynamics of necromass in woody Australian ecosystems. Issue 8 (5th August 2021) - Neumann, Mathias; Turner, John; Lewis, Tom; McCaw, Lachie; Cook, Gary; Adams, Mark A.
Abstract: Litterfall (LF) is the major contributor to aboveground necromass in ecosystems. Litter decomposition or litter decay (LD) then offsets deposition in LF, with the balance of LF and LD determining the standing litter (SL). SL together with fine and coarse woody debris (FWD, CWD) are the largest necromass pools. The interactions of LF, SL, and LD at continental scales reflect carbon and nutrient cycling and other ecosystem processes. We compiled data on leaf, twig (<2.6 cm), and other material (mostly bark and reproductive tissue) for SL and LF for the fire‐prone Australian continent, where SL is also a major "fuel load" and important for fire spread and fire intensity. We extracted data from 498 published and unpublished works (1825 LF observations; n SL = 3914; n LD = 629). We used Olson's (mass‐balance) approach ( k  ˜ LF/SL) to calculate LD for sites long undisturbed with both LF and SL data. We compiled LF and SL by component (leaves, twigs, other material) and metainformation such as sampling location, tree species, or time since fire from literature and/or scientists. Most data were available from warm‐seasonal (36% for SL) and cool‐wet (31%) climates, linking the locations of our data with a bio‐climate classification. Warm‐wet (20%) and hot‐seasonal (8%) climates followed, while other climate zones each contributed <2% of the data. Across all climatic zones, average SL (1100 g/m 2 ) was roughly twice that of LF (468 g·m −2 ·yr −1 ). SL was greatest in cold climates (2334 g/m 2 ), compared to warm‐wet (1168 g/m 2 ) and hot‐seasonal conditions (499 g/m 2 ). Important drivers of SL are LD (e.g., slow under cold conditions) and fire frequency. Olson's k varied with type of decomposing material ("composition"). For example, across the continent, k  ˜ 1.942 yr −1 for leaves but was 0.504 yr −1 for twigs. SL varied strongly in composition according to climate type (e.g., seasonal vs. wet climates). Robust models of necromass dynamics must distinguish between the litter components (such as leaves and twigs) and consider the complex and non‐linear effects of climate, stand structure, and stand history on litterfall and decomposition.